Determinants of Tax Revenue: The Mediating Role of Taxpayer Compliance in the Context of Indonesian Tax Offices - Rida Ristiyana; Mutia Dewi Junika; Erwindiawan Erwindiawan (Ilomata International Journal of Tax and Accounting, 2026)
Tax revenue at KPP Pratama Serang Barat has fluctuated in recent years and has not consistently reached the expected target. One of the factors causing this condition is the low level of compliance of taxpayers in fulfilling tax obligations, thus hindering the optimization of tax revenue. Therefore, this study aims to examine the effects of tax literacy, tax administration system, tax information technology on tax revenue with taxpayer compliance as a mediation variable. The role of taxpayer compliance mediation is used to explain how these factors affect tax revenue through taxpayer behavior and compliance. The study used a quantitative approach primary data through questionnaires. The population is an individual taxpayer registered at the KPP Pratama Serang Barat. The sampling technique used incidental sampling involving 100 respondents. The data analysis method uses PLS. The results show that the administrative system, information technology have a positive and significant effect on taxpayer compliance, whereas tax literacy has no effect on taxpayer compliance. The mediation effect test show that taxpayer compliance can strengthen the influence of administrative systems and information technology on tax revenue. However, taxpayer compliance cannot strengthen the influence of tax literacy on tax revenue. The research has implications for strengthening the administrative system, the use of information technology which is a strategic factor in increasing taxpayer compliance and tax revenue. Tax authorities must optimize the modernization of the tax system, expand education programs, and socialize tax literacy to increase tax awareness and compliance in a sustainable manner.